Communication Education for Teenagers to Strengthen Self-Concept in Avoiding Promiscuity - Muhamad Hanif Fuadi; Frista Fitriany Ramadhanita (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
Adolescence is a complex transition period, marked by moral challenges such as the increasing prevalence of free association due to technology and global culture. This study highlights communication education based on Islamic values as a preventive approach to strengthen teenagers' self-concept. Through interactive workshops and panel discussions, the program at Masjid Besar Lembang raised awareness among teenagers about the importance of interpersonal communication, self-control, and pre-marital education. Evaluation results show an increase in teenagers' understanding of self-concept in accordance with Islamic teachings, effective communication, and the negative impact of free association. This program contributes to the development of a morally and intellectually resilient youth generation, while emphasizing the importance of collaboration between family, school, and religious communities for such initiatives.